Assessment of heavy metals and its treatment through phytoremediation in groundwater along River Kabul in district Charsadda - Khan, Shehryar; Kamal, Masroor; Noor, Shah; Afzal, Syes Muhammad (Frontiers in Environmental Science, 2024)
Life cannot exist without water. Water scarcity is caused by massive groundwater decline. Water contamination is the most common problem spreading worldwide quicker than ever, along with anthropogenic water scarcity. Since tainted water can harm health, water contamination is also contributing to water scarcity. Heavy metals in drinking water have plagued most Asian, African, and European nations for decades. Studies reveal that heavy metals have caused damage in Pakistan, India, and China. This study detects heavy metals in groundwater and treats them with phytoremediation along the river Kabul in district Charsadda. It also measures pH, EC, TDS, turbidity, fluoride, phosphates, nitrites, and nitrates. All indicators meet the WHO and national environmental quality criteria for drinking water, except for turbidity, which exceeds the limit of ≤5 NTU in four examined regions, reaching a maximum of 9.99 NTU. Chemical parameters were within the standard limits, except for high concentrations of arsenic (As) and cadmium (Cd) in samples from S2 (15.20 μg/L) and S1 (20.50 μg/L) compared to WHO’s 10 and 5 μg/L standards. However, the limit is within EPA Pakistan’s 50 and 100 μg/L standards for drinking water, which Pakistan still follows. Heavy metals can harm health, even at low levels. Since the majority of the study area’s population relies on groundwater for drinking and other needs, heavy metal pollution of the groundwater can cause many ailments. Thus, phytoremediation is increasingly vital to reduce these heavy metals to WHO limits to protect human health and the environment.